Foam forming of fiber products: a review - Hjelt, Tuomo; Ketoja, Jukka A.; Kiiskinen, Harri; Koponen, Antti I.; Pääkkönen, Elina (Journal of dispersion science and technology, 2022)
Aqueous foam can be used as a transfer medium to form lightweight materials from natural and man-made fibers together with other types of raw materials. This review discusses mechanisms that underlie the forming process and thus influence physical properties of formed fiber networks such as microporous structure, strength behavior, and transport properties. Homogeneous fiber materials can be formed from versatile raw materials, which makes the technology suitable for a vast range of product applications. An intriguing feature of the method is that the wet foam characteristics provide an additional tool to tailor the performance of the dried material. Understanding foam rheology and how that is affected by added fibers is important in developing the forming process. We introduce both fundamental foam properties and practical forming methods, and show how the material properties are affected by the foam-fiber interaction. The basic features of an industrial production process are also described. The potential material properties are compared against key requirements in typical product applications.